2007
DOI: 10.5194/angeo-25-2541-2007
|View full text |Cite
|
Sign up to set email alerts
|

Quiet-condition variations in the scale height at F2-layer peak at Jicamarca during solar minimum and maximum

Abstract: Abstract. This study is the first attempt to examine the quiet-condition variations in scale height (Hm) near the F2-layer peak in the equatorial ionosphere. The data periods of Hm derived from the Jicamarca ionograms are JanuaryDecember 1996 and April 1999-March 2000. The results show that the greatest and smallest Hm values are generally at 11:00-12:00 LT and 04:00-05:00 LT, respectively. Additionally, the sunrise peak occurs at 06:00 LT only during solar minimum. The post-sunset peaks in the equinoctial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…also indicated that the uplift in the hmF 2 was driven by the vertical drift. Furthermore, we examined the ionospheric scale height around the peak height (H m ), which was considered to be associated with the sunrise during the daytime (Lee and Reinisch, 2007). The result showed a small fluctuation between 06:00 LT and 07:00 LT and an apparent increase at 07:00 LT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…also indicated that the uplift in the hmF 2 was driven by the vertical drift. Furthermore, we examined the ionospheric scale height around the peak height (H m ), which was considered to be associated with the sunrise during the daytime (Lee and Reinisch, 2007). The result showed a small fluctuation between 06:00 LT and 07:00 LT and an apparent increase at 07:00 LT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3.2. Lee and Reinisch (2007) studied the diurnal and seasonal variations of the scale height (H m ) at the F2 layer peak over a dip equatorial station Jicamarca and indicated that the diurnal variations of H m generally show the greatest value at 11:00 to 12:00 LT and that these values at noon are greater in the equinoctial and winter months. Liu et al (2008) investigated the local time, seasonal, latitudinal and longitudinal variations of Vertical Scale Height (VSH) with the COSMIC radio occultation measurements during low solar activity period (2006)(2007)(2008) and reported that the VSH values are higher during day-time, compared to those in the night-time with an outstanding peak around local noon and decreasing after noon till mid night.…”
Section: Variation Of Effective Scale Height (H T )mentioning
confidence: 99%
“…Zhang et al, 2006;Lee and Reinisch, 2007;Nambala et al, 2008, among others) and they can be useful for obtaining information for the topside-profile formulation from bottomside measurements and modelling. However, further studies and analyses are needed to validate analytical functions relating to the topside and bottomside parameters in order to contribute to the IRI modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Nsumei et al (2010) have evaluated the daily variations of the bottomside-derived H m at different latitudes, and have reported a latitude dependence in agreement with our current results. Moreover, the results reported by Zhang et al (2006), Lee and Reinisch (2007), and Nambala et al (2008), using data from Hainan (19.4 • N; 109.0 • E), Jicamarca (12.0…”
Section: Latitudinal Variationmentioning
confidence: 99%
See 1 more Smart Citation